Effective design of one-story wooden frame cages - Першаков, В.Н.; Романчук, О.М. (Proceedings of National Aviation University (archive), 2009)
Generalization and analysis of structural decisions of one-story wooden frame frameworks of industrial, civil and agricultural buildings is conducted. The most effective constructions and direction of their development are exposed.